Imajinasi Nasionalisme dalam Perspektif Teoritik Kebangsaan dan Agama - George Marthen Likumahwa; Mus J Huliselan; John A Titaley; Simon Pieter Soegijono (Program Pascasarjana UKIM, 2024)
This study presents a theoretical analysis of the imagination of nationalism which can become an epistemic anchor when discussing the idea of nationalism and its relevance for contemporary society. With a qualitative descriptive approach, the imagination of nationalism is analyzed as a theoretical perspective on nationalism which is very important when faced with various problems in global society today. These issues include the struggle for justice, freedom, human rights, and most recently the development of digitalization which can undermine the life of a nation. This theoretical idea of nationalistic imagination was built in discussing a social problem of indigenous peoples who were displaced by waves of capitalism that used state power to encroach on the living existence space of a group of indigenous peoples. This research, in the end, presents various theoretical perspectives regarding the imagination of nationalism which can enliven the discourse on various nationalist issues today.